State of the field: Latin American decolonial philosophies of science. (December 2019) - Harding, Sandra
Abstract: Today, new histories of science are producing skeptical questions about the supposedly international philosophies of science that prevail in the North. The conceptual resources of such philosophies seem inadequate to enable them to interact effectively with how sciences and their philosophies do, could, and should function in today's economic, political, social and cultural, local and global contexts. How international, or universal, are these philosophies of science in reality? Here the focus will be on just one strain of these challenges. This one has emerged from Latin Americans who are creating anti-colonial histories and philosophies of knowledge production. They have named it modernity/coloniality/decolonial theory (MCD). They intend to develop a philosophy of science adequate for its own, Latin American needs. In the process, they transform typical Northern assumptions about modernity, its origins and its effects on Northern philosophies of science, as these are understood in both Latin America and around the globe. Five aspects of the MCD accounts will be discussed here. The first is historical differences between the worlds of the Spanish and Portuguese colonization of the Americas in the sixteenth century and of the worlds of the mostly British colonization of India and Africa in the 'long nineteenth century'. Second is feminist and anti-racist issues in these Latin American histories. Third is the neglect of these histories in the North. Fourth is the continuing effects of the rise and fall of a positivist philosophy of science in Latin America. The fifth is two progressive post-positivist tensions for Northern philosophy of science produced in this work. Highlights: Transform accounts of origins and effects of modernity. Challenge accuracy of Northern histories and philosophies of science. Develop Latin American philosophies of science.